National Library of Malaysia: A legal perspective view / Azmi Ab Rahman, Abdul Rahman Ahmad and Ahmad Nazri Mansor - Ab Rahman, Azmi; Ahmad, Abdul Rahman; Mansor, Ahmad Nazri (Faculty of Information Management, 2015)
National Library of Malaysia (PNM) is the premier library in Malaysia that overlooks the development of libraries all over the country. PNM started humbly in 1966 and now stand tall among the national libraries throughout the world. The purpose of this article is to explain the jurisdiction vested on PNM through National Library Act 1972, the article discuss the aspects of power exercised by PNM by virtue of rules and regulations that has been laid down by legislative power and cannot be denied by anyone else.